Preference for Molineria latifolia var. megacarpa and Rhodomyrtus tomentosa as native urban landscape plants - Baharudin, Sarah; Abdullah, Thohirah Lee; Mohd Shariff, Mustafa Kamal; Abu Bakar, Rosenani (Universiti Putra Malaysia Press, 2014)
Factors influencing the perception of landscapes have been the subject of research in the last 40 years. Indigenous and native plants are commonly restricted to informal or naturalistic designed landscapes. This research project investigates the use of native plants as a formal landscape element. As the world is becoming more urbanized (United Nations, 2010), gardens are becoming an increasingly important contributor to people’s health and well-being (Dunnett & Qasim, 2000). The research has highlighted some elements that tend to affect visual preferences. This paper discusses a study conducted to determine preferences of Malaysian landscape professionals and students in landscape architecture and horticulture on two native ornamental plants, Molineria latifolia var. megacarpa (Lemba) and Rhodomyrtus tomentosa (Kemunting), that are grown in soilless media with the potential for use in urban landscapes. Participants of this study comprised of landscape architects (20 respondents), architects (20), nursery owners (20), Bachelor of Horticulture students (80) (Faculty of Agriculture, UPM), and Bachelor of Landscape Architecture students (80 respondents) (Faculty of Design and Architecture, UPM), with a total of 220 respondents. Data collected were analyzed through descriptive analysis, Chi square and reliability test using SPSS. Results indicated that 88.2% of the respondents agreed that Molineria latifolia var. megacarpa (Lemba) could be a potential urban landscape plant, while 92.7% of them agreed that Rhodomyrtus tomentosa (Kemunting) could be domesticated, and is therefore a potential urban landscape plant. Majority of the respondents (49% to 55%) preferred the plants grown individually, while others (40% to 49%) preferred both plants in the form of mass planting. Meanwhile, using the Likert’s Scale, about half (50% to 52%) of the amateurs and professionals of the landscape field rated 4 (Like) for both the plants, whereas 10% to 15% of them marked 5 (Extremely Like) to show their acceptance towards the two new native plants. This finding indicates bright future for the two undomesticated wild native plants to be used as urban landscape plants. Thus, it is concluded that Molineria latifolia var. megacarpa (Lemba) and Rhodomyrtus tomentosa (Kemunting) grown in soilless media have a high potential to become urban, native landscape plants.